2020
DOI: 10.7759/cureus.6904
|View full text |Cite
|
Sign up to set email alerts
|

Scoliosis Associated with Lumbar Spondylolisthesis: Spontaneous Resolution and Seven-Year Follow-Up

Abstract: Scoliosis is defined as a structural deformity of the spine in all three dimensions and diagnosed if the Cobb angle is ≥10 degrees. Scoliosis is frequently associated with symptomatic spondylolisthesis, with an incidence ranging from 15% to 48%. The present report describes a patient with scoliosis associated with grade IV lumbar dysplastic spondylolisthesis who experienced the spontaneous correction of scoliosis after spondylolisthesis correction and fixation. The patient was a 12-year-old girl premenarche wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…A: Preoperative radiograph demonstrated obvious trunk tilt and vertebral rotation at the thoracolumbar spine; we believe the scoliosis was composed of idiopathic scoliosis and spondylolisthesis-induced scoliosis (54°). B: Postoperative radiograph at two-year follow-up shows relief of spondylolisthesis-induced scoliosis with normal coronal balance, while the idiopathic scoliosis was restored to its "original" shape (43°) accompanied by a large Cobb angle (20° or more), which can be confused with idiopathic scoliosis [10,12,[16][17][18][19][20]. It is important to distinguish the two cases, because the former can be relieved with reduction and fixation of the slip while the latter cannot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A: Preoperative radiograph demonstrated obvious trunk tilt and vertebral rotation at the thoracolumbar spine; we believe the scoliosis was composed of idiopathic scoliosis and spondylolisthesis-induced scoliosis (54°). B: Postoperative radiograph at two-year follow-up shows relief of spondylolisthesis-induced scoliosis with normal coronal balance, while the idiopathic scoliosis was restored to its "original" shape (43°) accompanied by a large Cobb angle (20° or more), which can be confused with idiopathic scoliosis [10,12,[16][17][18][19][20]. It is important to distinguish the two cases, because the former can be relieved with reduction and fixation of the slip while the latter cannot.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to distinguish the two cases, because the former can be relieved with reduction and fixation of the slip while the latter cannot. Several authors have reported complete resolution of severe scoliosis associated with spondylolisthesis after operative treatment of spondylolisthesis (Table 5) [17][18][19][20]. The scoliosis in these cases, with almost no vertebral rotation but large Cobb angle and marked coronal imbalance, should be considered as spasm scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…3 Scoliosis and spondylolisthesis are complex conditions that can be grouped into three main categories: idiopathic, radicular, and olisthetic. 4,5 Khashab et al 6 found that for patients with scoliosis caused by spondylolisthesis, surgery may only be needed for the latter condition, greatly improving symptoms and spinal curvature and avoiding unnecessary scoliosis surgery. In the treatment of L5 spondylolisthesis with accompanying scoliosis, Du et al 7 achieved a satisfactory reduction of slippage and correction of spinal curvature through transforaminal lumbar interbody fusion (TLIF).…”
Section: Introductionmentioning
confidence: 99%
“…Scoliosis and spondylolisthesis are complex conditions that can be grouped into three main categories: idiopathic, radicular, and olisthetic 4,5 . Khashab et al 6 . found that for patients with scoliosis caused by spondylolisthesis, surgery may only be needed for the latter condition, greatly improving symptoms and spinal curvature and avoiding unnecessary scoliosis surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation